Price Elasticities of Food Demand: Compensated vs Uncompensated. (2nd September 2015) - Clements, Kenneth W.; Si, Jiawei
Abstract: Two recent studies have provided a comprehensive review/summary of a large number of estimates of the price elasticity of food consumption using a meta‐regression approach. In this letter, we introduce a way of removing the income effect from these elasticities to recover the compensated elasticities. Although the income effect is small, the compensated elasticities vary by income group. Both types of elasticity should possibly be considered when assessing the impact of policy changes on food consumption. Copyright © 2015 John Wiley & Sons, Ltd.